A broadband circularly polarized monopole antenna. Issue 6 (31st December 2018) - Li, Zhen‐Ya; Zhu, Xiao‐Song; Yin, Cheng‐You; Huang, Ye
Abstract: A compact modified C‐shaped monopole antenna with broadband circular polarization is proposed, fabricated and measured. The antenna structure is simple and only consists of combined modified C‐shaped radiation patch and an improved ground plane with the overall size of 25 × 25 × 1 mm 3 . By cutting the corner on the modified C‐shaped patch and adding triangular stubs on the ground plane, the wide impedance bandwidth and axial ratio bandwidth are achieved. The design process of the antenna is given, and the circular polarization mechanism of the circularly polarized antenna is analyzed from the surface current distributions. The measured impedance bandwidth is 95.2% (4.4‐12.4 GHz) with return loss better than 10 dB, and the measured 3 dB axial ratio bandwidth is 96.8% (4.42‐12.72 GHz). The peak gain is above 3.0 dBi within the working band, which indicates that it is suitable for application of ultra‐wideband (UWB) wireless communication systems and satellite communication systems.